Omega-3 and omega-6 consumption in a sample group of portuguese women - Lucas, C. (2021)
The present study had as its main objective the evaluation of the consumption of polyunsaturated fatty acids (PUFA), omegas 3 (n-3) and 6 (n-6). The sample consisted of six women over 40 years old, living in Lisbon. A cross-sectional analysis of the consumption of omega-3 and 6 was made through the application of a 3-day food diary (2 weekdays and 1 weekend day), and later analysis of the data by the FoodProcessor program. The results showed that there was an inadequate intake of n-3 and n-6 PUFAs. Further analysis showed that n-6 intake was high (84%) in comparison to n-3 intake (16%), and the ratio of n-6 and n-3 intake was not in line with recommendations. The results of this study suggest that the sample presents an inadequate intake of n-3 and n-6 PUFA, and it is necessary to emphasize the importance of nutritional programs in order to reduce the probability of occurrence of certain pathologies associated with imbalance of n-6 / n-3 intake. © 2019 ALIES. All rights reserved